LITERASI MASYARAKAT TERHADAP PENYEBARAN BERITA-BERITA VIRAL INTERNET DAN HUBUNGANNYA DENGAN KETAHANAN NASIONAL - subarjo, abdul haris (SENATIK STT Adisutjipto, 2017)
STTA is an academic institution, because of the resion important to research in this institution. The research has aim to known literacy profile in academic society . Focus this research is information in internet or social media and reseliance.This research is a descriptive. The research focused in social media viral news with the reseliance. Sample of the research with the purposive cluster sampling, with the student STTA is a sample. Department is a cluster. Quesioner and writing tes is an instrument.From the data there are many  conclution. Improved of information literacy is important to the responden.The benefit from the data, we can knows that information can be fast to transmited. The information can be viral information. But the hoax information can be froud in the society. Thishoax information can be danger to the nasional resilience.